MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS ASESMEN KINERJA DAN BAKAT NUMERIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA - I Komang Sukendra; I Wayan Sumandya (LP3M Universitas PGRI Mahadewa Indonesia, 2018)
This study aims to find out the interaction and influence of problem based learning model based on performance assessment and numerical talents towards the learning outcomes of mathematics learners. Type of research in this research is quasi experimental research (Quasi Experiment). This study has a control group, but not entirely to control external variables that influence the execution of experiments. Research design used in this experiment is Treatment By Level (2x2) where one of its independent variables will serve as moderator variable. The population of the study was all students of grade X SMA N 7 Denpasar in Year 2016/2017 for 9 classes of IPA and 3 classes of IPS with 430 people. Samples were selected as 4 classes, namely class X IPA 2 and X IPA 4 as experimental group and class X IPA 6 and X IPA 7 as control group with multistage random sampling technique. The instrument in the research is a method of mathematics learning outcomes and numerical talent tests. The data were analyzed by using two-way ANAVA hypothesis and Tukey Test. Based on the results of the Anova two paths shows that the value of F for AxB interaction is obtained Fhitung of 13.72, while Ftabel with 5% significance level and dbD 76 is 3.97. It shows that Fhitung> Ftable (0.05) (1.76) (13.72> 3.97), so that the null hypothesis (Ho) is rejected and H1 is accepted. Based on the result of Tukey test, Qhitung counted 6,19 while Qtabel for significance level 5%, with k = 4 and n = 20 equal to 3,96. It turns Qhitung> Qtabel (0,05) (4,20), (6,19> 3,96), so the null hypothesis (Ho) is rejected and H1 is accepted. From the results of the data analysis it was found that: (1) there was interaction between learning model and numerical talent of learners toward mathematics learning result (2) there was difference of learning result of mathematics between student who follow problem based learning model based on performance assessment with students following conventional model (3) there is a difference in the learning outcomes of mathematics among students who follow a problem based learning model based on performance assessment with learners following the conventional model of learners who have low numerical talent. Based on the findings, it can be concluded that there is an interaction and influence of problem-based learning model based on performance assessment and numerical talents towards the achievement of mathematics learning outcomes of X grade students of SMA N 7 Denpasar Year of Education 2016/2017.